Spatial distribution of driftwood on Svalbard - Urbański, Jacek (Polish Polar Research, 2026)
The driftwood trajectories derived from a model describing sea ice drift and surface water currents show that 24% of wood logs entering the Arctic Ocean from the rivers of Western Siberia, such as the Pechora, Ob, and Yenisey, are deposited along the coasts of Svalbard. Satellite-based mapping of driftwood along the entire Svalbard coastline revealed its clustered distribution. The highest concentrations occur on the northern shores of Spitsbergen and Nordaustlandet (32%), as well as along the shores of Prins Karls Forland (24%). The majority of tree trunks, measuring 2–6 m in length, is located 20–200 m inland and at elevations of 3–8 m a.s.l. River mouths and lagoons play an important role in the local distribution of driftwood. A rough estimate suggests that Svalbard contains between 100 000 and 300 000 driftwood logs.